Emotionally intelligent leadership : a guide for students - Levy Shankman, Marcy; Allen, Scott J., 1972-; Haber-Curran, Paige (San Francisco, CA : Jossey-Bass, a Wiley brand, 2015)
'Explores the connection between emotional intelligence and effective leadership'--
Includes bibliographical references and index.
Keywords: Educational leadership; Teacher effectiveness; Emotional intelligence